PERBANDINGAN LIFE SKILL ANTARA JIGSAW DAN VCT DENGAN MEMPERHATIKAN KONSEP DIRI - Andreas Saut H. Malau; Edy Purnomo; Yon Rizal (JEE (Jurnal Edukasi Ekobis), 2015)
This research examined the comparative study of Life Skills between students who where taught using cooperative learning model of Jigsaw and VCT (Value Clarification Technique) based on the self concept of students at class VIII of SMP Negeri 4 Gadingrejo Pringsewu. The method of the research is comparative with experimental approaches. The result of data analysis showed that (1) There is a difference life skills of students who used jigsaw learning model than those who used VCT (Value Clarification Technique). (2) Life Skills of students who used Jigsaw Learning Model is higher than those who used VCT (Value Clarification Technique) on the students who have the positive self concept. (3) Life skills of students who used Jigsaw is lower than using VCT (Value Clarification Technique) in the students who have negative self concept. (4) There is an interaction between learning models with the self concept of students to Life skills in the subject of Integrated social studies.Penelitian ini mengkaji tentang perbandingan Life Skill antara model pembelajaran Jigsaw dan VCT (Value Clarification Technique) dengan memperhatikan konsep diri pada siswa kelas VIII SMP Negeri 4 Gadingrejo Pringsewu. Metode yang digunakan adalah komparatif dengan pendekatan eksperimen. Hasil analisis data menunjukkan (1) Ada perbedaan life skill siswa yang pembelajarannya menggunakan model pembelajaran Jigsaw dibandingkan menggunakan model pembelajaran VCT (Value Clarification Technique). (2) Life Skill siswa yang pembelajarannya menggunakan model pembelajaran Jigsaw lebih tinggi dibandingkan menggunakan VCT (Value Clarification Technique) pada siswa yang memiliki konsep diri yang positif. (3) Life Skill Siswa yang pembelajarannya menggunakan model pembelajaran Jigsaw lebih rendah dibandingkan menggunakan VCT (Value Clarification Technique) pada siswa yang memiliki konsep diri yang negatif. (4) Ada interaksi antara model pembelajaran dengan konsep diri siswa terhadap Life Skill pada mata pelajaran IPS Terpadu.Kata kunci: life skill, konsep diri, jigsaw, VCT